Photonic, magnetic and metallomesogenic properties of Cu(ii), Ni(ii), Co(ii), Fe(ii) and Mn(ii)/Mn(iii) complexes with alkylcarboxylates, schiff bases and cyclam as ligands / Yanti Yana Halid - Yanti Yana, Halid (2016)
The main objective of this research was to synthesis and study the photonic, magnetic and metallomesogenic properties of Cu(II), Ni(II), Co(II), Fe(II) and Mn(II)/Mn(III) with alkylcarboxylates, Schiff bases and cyclam as ligands. Three new Schiff bases (H2L1, H2L2 and H2L3) were successfully obtained from the condensation reactions of 1,8-diaminooctane with 2-hydroxybenzaldehyde, 2,4-dihydroxybenzaldehyde, and 3,5-di(tert-butyl)benzaldehyde, respectively. A total of twenty-two (22) complexes were successfully synthesised. The structures of these complexes were deduced from 1H-NMR (for ligands), X-ray crystallography (for crystals), elemental analyses, FTIR and UV-visible spectroscopies, their band gap were determined from UV-visible, fluorescence spectroscopies and cyclic voltammetry, their room-temperature magnetic susceptibilities by the Gouy method and their thermal and mesomorphic properties by themogravimetry (TG), optical polarizing microscopy (OPM) and differential scanning calorimetry (DSC). All Cu(II), Fe(II) and cyclam complexes were mononuclear, while all Ni(II), Co(II) and Mn(II)/Mn(III) complexes were dinuclear. The optical band gaps of these complexes were in the range of 0.31 eV to 3.61 eV and the lifetimes were in the range of 0.7 ns to 3.9 ns. All complexes were paramagnetic, and their decomposition temperatures were in the range of 134 °C to 301 °C. Finally, only [Mn2(R)2(L1)(H2O)4].2H2O, [Ni(R’)(cyclam)]R’.4H2O and [Co(R’)2(cyclam)].R’H, (where R = CH3COO and R’ = CH3(CH2)14COO) were mesomorphic.